Florida Plant Disease Management Guide: 'Tahiti' Lime (Citrus latifolia) - Tara Tarnowski; Aaron J. Palmateer; Ian Maguire; Jonathan H. Crane (EDIS)
Revised! PP24, a 9-page illustrated fact sheet by Tara Tarnowski, Aaron J. Palmateer, Ian Maguire, and Jonathan H. Crane, provides an overview of disease management for 'Tahiti' lime, with symptoms, casual organisms/agents, disease cycle and epidemiology, and management information for several key diseases. Includes references. Published by the UF Department of Plant Pathology, October 2009.